Isoniazid Microencapsulation With HPMCP HP-50 and HPMCP HP-55 (2:3) Coating Using Solvent Evaporation Method - Hestiary Ratih; Gladdis Kamilah Pratiwi; Fikri Alatas; Mia Agustin; Bella Dewinta Saraswati (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
The combination formulation of TB drugs may cause interactions if these drugs are given simultaneously. Rifampin (RIF) decomposes in the stomach when given concurrently with isoniazid (INH), which results in a decrease in the bioavailability of RIF. The purpose of this study is to make INH microcapsules using HPMCP HP-50 and HP-55 coatings to prevent these interactions. The process of making INH: HPMCP HP-50 and HP-55 (2:3) microcapsules was done by using solvent evaporation method. The entrapment efficiency of INH: HPMCP HP-50 and HP-55 (2:3) were 83.21% and 91.57%, respectively. The dissolution test of INH: HPMCP HP-50 and HP-55 microcapsules met the requirements of the Indonesian Pharmacopoeia Edition V. The FTIR test showed that the microcapsules didn’t change the chemical composition of isoniazid or the coating on the microencapsulation so that it was concluded that no chemical reaction or decomposition occurred before and after the formation of the microcapsules. Scanning Electron Microscopy (SEM) showed a spherical microcapsule surface morphology and the active substance was well coated for INH: HPMCP HP-50 (2:3), while for INH: HPMCP HP-55 (2:3) the surface of the microcapsules was round but hollow. This study produces microcapsules that can provide a delayed release effect, so it is expected that INH: HPMCP HP-50 and HP-55 (2:3) microcapsules can be released in the intestines without interacting with RIF.